Protective effects of melatonin against ethanol-induced reactive gliosis in hippocampus and cortex of young and aged rats - Baydas, G; Tuzcu, M (Academic Press Inc Elsevier Science, 2005)
Evidence has been accumulated indicating that chronic ethanol consumption leads to direct or indirect changes in the viability of central nervous system cells. The effects of aging and chronic ethanol consumption on glial markers [glial fibrillary acidic protein (GFAP) and S100B] and oxidant and antioxidant status of rats were studied. Furthermore, protective effects of melatonin against aging and alcohol consumption were also assayed. Chronic ethanol administration to young and aged rats produced an increase in lipid peroxidation, and a decline in glutathione (GSH) levels, which was significantly reversed by the co-administration of melatonin. Lipid peroxidation status was markedly affected in aged rats treated with alcohol compared to the young rats. An age-related increase in GFAP and S100B levels were found in the cortex and hippocampus. Long-term alcohol exposure resulted in distinct elevation in GFAP content in young rats (P < 0.01) while there was less increase in the cortex of aged rats (P < 0.05). In old rats, hippocampat GFAP levels were not significantly changed by alcohol treatment (P > 0.05). Co-administration of melatonin with alcohol significantly reduced GFAP contents both in the hippocampus (P < 0.01) and cortex (P < 0.001) of aged rats. No significant effects of alcohol treatment were found on the levels of neuron-specific enolase (NSE) in aged rats. This finding suggests that melatonin exerts its protective effect on injured nervous tissues by scavenging free radicals and stabilizing glial activity against the damaging effects of ethanol and aging. Furthermore, this work suggests that the signal to initiate gliosis is mediated, at least indirectly, by free radical formation. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: glial fibrillary acidic proteins; S100B proteinsn; euron-specific enolase; lipid peroxidation; glutathione